Immersion Program in Arabic Language Learning: An Analysis of Teachers and Students - R.U., Nafisatul Izza; Iswar, Nabila Salsabila; Murtadho, Nurul; Eltingari, Salih (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Learning Arabic through immersion programs has a significant impact on improving language skills. This study explores the differences in the implementation of immersion programs between domestic and foreign institutions with a focus on teacher performance and student achievement. The lack of comparative studies in this area motivates more in-depth analyses to understand the variation in effectiveness. The literature study approach compares teaching practices and learning outcomes in both contexts. The study results revealed that the immersion program improved students' Arabic language skills by up to 54.0%. However, there was a variation in success between domestic and international institutions. This difference is mainly due to different teaching approaches and the use of learning media. Teachers abroad use student-centred communicative methods, while traditional methods dominate domestically. In addition, the use of educational technology is more optimal abroad, which has an impact on student learning outcomes. This study's implications emphasise adapting immersion programs tailored to local characteristics. The exchange of best practices between domestic and foreign institutions and the continuous training of teachers is essential to improve the effectiveness of Arabic language learning globally.